(untitled) (International Conference on Energy, Intelligence Systems, and Cloud Computing (Ingenio 2026), 2026)
With the increasing penetration of renewable energy sources in the power grid due to the high proportion of renewable energy integration, a system architecture is proposed for joint participation of wind, solar, and electric energy storage in both the energy market and frequency regulation ancillary service mar ket. To improve the implementation accuracy of day-ahead schedules, a deviation penalty mechanism is introduced. Considering uncertainties in wind power, solar irradiance amplitude, a day-ahead and real-time coordinated bidding model based on typical scenarios is constructed to maximize the overall expected economic benefit of the integrated system. Simulation verification proves that compared to separate bidding for wind and solar power, joint bidding can mitigate bidding deviation penalties caused by wind power fluctuations through the flexible ad justment characteristics of electric energy storage, thereby enhancing the overall revenue of the joint system.